2009
DOI: 10.1111/j.1462-2920.2009.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards functional molecular fingerprints

Abstract: One of the most important challenges in microbial ecology is to determine the ecological function of dominant microbial populations in their environment. In this paper we propose a generic method coupling fingerprinting and mathematical tools to achieve the functional assigning of bacteria detected in microbial consortia. This approach was tested on a nitrification bioprocess where two functions carried out by two different communities could be clearly distinguished. The mathematical theory of observers of dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 23 publications
(27 reference statements)
1
29
0
Order By: Relevance
“…Except for some well-identified periods, the experiment was run in duplicate and both chemostats behaved similarly. For this reason, in the present study we concentrate on the results obtained from only one device (the chemostat denoted as "chemostat B" in [31]). The main results of this monitoring-on average over the 525 days of experiments-were (i) 40% of the total biomass was represented by the most abundant AOB; (ii) the most abundant NOB represented less than 10% of the total biomass; (iii) the two most abundant AOB and the two most abundant NOB represented more than 55% of the total biomass.…”
Section: Microbial Community Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Except for some well-identified periods, the experiment was run in duplicate and both chemostats behaved similarly. For this reason, in the present study we concentrate on the results obtained from only one device (the chemostat denoted as "chemostat B" in [31]). The main results of this monitoring-on average over the 525 days of experiments-were (i) 40% of the total biomass was represented by the most abundant AOB; (ii) the most abundant NOB represented less than 10% of the total biomass; (iii) the two most abundant AOB and the two most abundant NOB represented more than 55% of the total biomass.…”
Section: Microbial Community Measurementsmentioning
confidence: 99%
“…However, it is not what is observed in practice (cf. the data we use from [31]: we will come back on these data later on but it will be clearly shown that the dynamics of AOB1 and AOB2, and of NOB1 and NOB2, are significantly different). Now, with different growth rates and again no interactions, the competitive exclusion principle applies and coexistence is simply not possible.…”
Section: Identification Of the Parameters Of Microbial Interactionmentioning
confidence: 99%
See 3 more Smart Citations